Pulmonary Alveolar Proteinosis due to Familial Myelodysplastic Syndrome with resolution after stem cell transplant - Amjad Basheer; Eduardo Messias Hirano Padrao; Kangwook Huh; Susan Parker; Tejal Shah; Daniel A. Gerardi (University of São Paulo, 2022)
Pulmonary alveolar proteinosis (PAP) is a rare lung disease with an incidence of 0.2 cases per million. PAP has multiple causes, including autoimmune, hereditary, congenital, or secondary. The latter includes hematologic conditions and exposure to different kinds of dust. Most patients present fever, dyspnea, and cough. The chest computed tomography (CT) may reveal the crazy-paving polygonal shapes with superimposed ground glass opacities delimited by thickened interlobular septa; however, this finding is more prevalent in patients with autoimmune PAP. Bronchoalveolar lavage (BAL) shows a milky-opaque appearance with PAS-positive debris on cytology. Treatment is focused on the underlying disease; however, some patients may require whole lung lavage for symptomatic management. We report a case of a 30-year-old female with a history of familial myelodysplastic syndrome (MDS) with GATA 2 mutation who presented to the outpatient clinic with several months of progressive dyspnea and nonproductive cough. The chest CT revealed bilateral ground-glass opacities prominently in the upper lobes. She underwent a bronchoscopy with lavage and biopsy, which revealed fragments of lung parenchyma with intra-alveolar coarse granular eosinophilic material strongly positive for PAS and d-PAS. The overall clinical presentation and histologic findings were diagnostic of PAP. Her GM-CSF was negative, and due to her history of MDS, secondary PAP (S-PAP) was strongly suspected. She underwent a successful allogeneic bone marrow pluripotent stem cell transplant to treat the myelodysplastic syndrome, with a follow-up chest CT showing clear lung parenchyma. The patient had resolution of symptoms about four months after the bone marrow transplant, confirming the diagnosis of S-PAP.